The journey from the veterinary operating table to the chief observer for home affairs education: Interview with 75-year-old retired police major general Prof. Dr. Frigyes Janza (Academic Journal of Internal Affairs, 2022)
Frigyes Janza was born on 8 April 1947 in Újpest. Since 1971, he has held several positions in the Ministry of the Interior. This means that he has spent nearly 70% of his life as a home affairs member. As a former civilian employee, he was a veterinarian in Dunakeszi, at the BM Dog Handler Training School he operated a veterinary hospital, then as a professional officer he became the commander of the school. Success followed success, whatever he touched, something new, something miraculous was born. He became a leading figure in dog breeding and the training and education of service dog handlers in our country and has become a recognised and sought-after expert throughout Europe. In just a few years, police service dog handlers have come out on top at the European Drugs and Explosives Detection Dog Championships on several occasions. His name is also connected with the revival of the traditions of domestic horse breeding. As the head of the Service Animal Inspectorate, he supervised the professional activities at the Somogysárd equestrian base and established the National Equestrian Ceremonial Unit of the Republic. His monograph “Ethology” is still one of the most frequently consulted source materials among the professionals. His innovative, creative thinking and outstanding achievements in education and training were quickly noticed by the leadership of the Ministry of Interior. Therefore, it is no wonder that in 1998 he was appointed Head of the Education Department of the Ministry of the Interior. Although he never broke away from his original profession, today’s generation respects him more for his pioneering work in police training, and especially for his role in the establishment and operation of the University of Public Service. Today, as the Chief Education Observer of the Ministry of the Interior, he is involved in the dynamism of the education, training and further training system of the law enforcement field, and he is working with untiring enthusiasm to modernise a better system that meets the challenges of the times. His awards for his outstanding professional work, teaching and scientific organisation activities are hard to list. Among others, he is the owner of the Imre Kertész Prize, the András Szabó Medal, the title of Professor Emeritus, the Officer’s Cross Order of Merit of Hungary, the Knight’s Cross of the Order of Merit of Hungary, the St. George Medal, the Grand Cross of the Order of Merit of the Loyalty of Homeland, the Commemorative Medal for Outstanding Scientific Work. At its meeting in July 2020, the Senate of the University of Public Service, unanimously elected him honorary citizen of the institution, and also awarded him with a Kossuth-colt gift for his outstanding role in the founding and operation of the university. In the interview, the editor-in-chief of Belügyi Szemle, a decades-long comradein-arms of the interviewee, asked Prof. Dr. Frigyes Janza, ret. pol. major general, how and why he replaced his veterinary profession with the profession of human resource development in the public service.
Keywords: interview; education; training; dog handler training